Analysis of queuosine and 2-thio tRNA modifications by high throughput sequencing. Issue 17 (17th June 2022) - Katanski, Christopher D; Watkins, Christopher P; Zhang, Wen; Reyer, Matthew; Miller, Samuel; Pan, Tao
Abstract: Queuosine (Q) is a conserved tRNA modification at the wobble anticodon position of tRNAs that read the codons of amino acids Tyr, His, Asn, and Asp. Q-modification in tRNA plays important roles in the regulation of translation efficiency and fidelity. Queuosine tRNA modification is synthesized de novo in bacteria, whereas in mammals the substrate for Q-modification in tRNA is queuine, the catabolic product of the Q-base of gut bacteria. This gut microbiome dependent tRNA modification may play pivotal roles in translational regulation in different cellular contexts, but extensive studies of Q-modification biology are hindered by the lack of high throughput sequencing methods for its detection and quantitation. Here, we describe a periodate-treatment method that enables single base resolution profiling of Q-modification in tRNAs by Nextgen sequencing from biological RNA samples. Periodate oxidizes the Q-base, which results in specific deletion signatures in the RNA-seq data. Unexpectedly, we found that periodate-treatment also enables the detection of several 2-thio-modifications including τm 5 s 2 U, mcm 5 s 2 U, cmnm 5 s 2 U, and s 2 C by sequencing in human and E. coli tRNA. We term this method p eriodate-dependent a nalysis of q ueuosine and s ulfur modification sequencing (PAQS-seq). We assess Q- and 2-thio-modifications at the tRNA isodecoder level, and 2-thio modification changes in stress response. PAQS-seq should be widely applicable in the biological studies of Q- and 2-thio-modifications in mammalian and microbial tRNAs.